The substitute The substitute 2, The substitute 3, the Substitute 4 - Mandel, Robert; Berenger, Tom, 1950-; Hudson, Ernie; Lionsgate Entertainment (Firm) (Santa Monica. Calif. : Lionsgate, 1996)
Posing as a teacher, Shale and his team of mercenaries set a trap to catch the ringleaders of a ruthless gang of teenagers.
Title from container.
Director of photography, Bruce Surtees; editor, Alex Mackie; music by Gary Chang.
Tom Berenger, Ernie Hudson, Diane Venora, Glenn Plummer, Marc Anthony, Luis Guzman, william Forsythe.
Rated R.
VHS; hi-fi; Dolby surround stereo.
Closed captioned for the hearing impaired.
Keywords: Gangs -- Drama; Teachers -- Drama; Films for the hearing impaired; Feature films